Managing psychological safety in debriefings: a dynamic balancing act. (19th August 2019) - Kolbe, Michaela; Eppich, Walter; Rudolph, Jenny; Meguerdichian, Michael; Catena, Helen; Cripps, Amy; Grant, Vincent; Cheng, Adam
Abstract : Debriefings should promote reflection and help learners make sense of events. Threats to psychological safety can undermine reflective learning conversations and may inhibit transfer of key lessons from simulated cases to the general patient care context. Therefore, effective debriefings require high degrees of psychological safety—the perception that it is safe to take interpersonal risks and that one will not be embarrassed, rejected or otherwise punished for speaking their mind, not knowing or asking questions. The role of introductions, learning contracts and prebriefing in establishing psychological safety is well described in the literature. How to maintain psychological safety, while also being able to identify and restore psychological safety during debriefings, is less well understood. This review has several aims. First, we provide a detailed definition of psychological safety and justify its importance for debriefings. Second, we recommend specific strategies debriefers can use throughout the debriefing to build and maintain psychological safety. We base these recommendations on a literature review and on our own experiences as simulation educators. Third, we examine how debriefers might actively address perceived breaches to restore psychological safety. Re-establishing psychological safety after temporary threats or breaches can seem particularly daunting. To demystify this process, we invoke the metaphor of a 'safe container' for learning; a space where learners can feel secure enough to work at the edge of expertise without threat of humiliation. We conclude with a discussion of limitations and implications, particularly with respect to faculty development.